2006
DOI: 10.1159/000097639
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factor, Pattern, Etiology and Outcome in Ischemic Stroke Patients with Cancer: A Nested Case-Control Study

Abstract: Background: Coagulation disorders are seen in cancer patients, but it is not clear whether cancer predisposes stroke patients to unique characteristics. The aim of the study was to investigate risk factors, pattern,etiology and outcome in stroke patients with cancer. Methods: A retrospective review of all ischemic stroke (IS) patients with cancer (n = 56) admitted to Bankstown-Lidcombe Hospital, Sydney, Australia, between January 1999 and December 2004 was conducted and comparison made to age- and gender-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 39 publications
5
43
0
1
Order By: Relevance
“…However, Zhang et al came to the conclusion that cancer patients with stroke have a more dismal prognosis, probably due to their general state and the concurrence of two severe diseases (10,11).…”
Section: Quantity Of Stroke and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…However, Zhang et al came to the conclusion that cancer patients with stroke have a more dismal prognosis, probably due to their general state and the concurrence of two severe diseases (10,11).…”
Section: Quantity Of Stroke and Cancermentioning
confidence: 99%
“…In this study, the risk of recurrent ischaemic events was also similar to that of the non-cancer population. Recent articles compare cancer patients with a non-cancer population by means of image-based classifications and common risk factors for stroke (7)(8)(9)(10)(11). Concerning the studies, they all suffer from referral bias, which is less marked in general hospitals than in cancer centres.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that the stroke patterns and vascular risk factors in cancer patients were not significantly different compared with the general population. [5][6][7] Autopsy studies demonstrated that the most common cause of ischemic stroke (78% asymptomatic) in patients with cancer was atherosclerosis. 1 On the contrary, others reported that embolisms, not including those of cardiac origin, were the most common cause of ischemic stroke in cancer patients.…”
mentioning
confidence: 99%
“…4,5 A small number of earlier studies on this topic generated conflicting results. [6][7][8][9][10][11][12] The largest study including 161 patients by Kim et al in 2010 differentiated between patients with cancer+stroke with and without conventional stroke etiologies and renewed the idea of cancer-associated hypercoagulation as an important stroke etiology. 13 Significantly higher d-dimer levels as well as a significantly higher rate of multiply affected vascular territories in the group of patients without conventional stroke etiology supported the idea of cancer-associated hypercoagulation with resulting cerebral embolism.…”
mentioning
confidence: 99%